The influence of teacher-student proximity, teacher feedback, and near-seated peer groups on classroom engagement: An agent-based modeling approach. - Zhe Dong; Haiyan Liu; Xinqi Zheng (PLoS ONE, 2021)
Fostering students' classroom engagement is a research hotspot in classroom teaching management. Enhancing classroom engagement requires consideration of the interactive effects of physical and interpersonal environments. Considering the characteristics of physical space, the teacher gives feedback on student engagement in terms of different seating positions. Further, near-seated peer group engagement has an impact, though previous research has found this to be inconsistent. The teacher and near-seated peer groups have different paths of influence on classroom engagement, and there is interplay between them. However, based on realistic classroom scenarios, it is difficult for traditional research methods to reveal how spatially heterogeneous and non-linear micro-interactions among teachers, students, and near-seated peer groups evolve into dynamic changes in macro-classroom engagement. Hence, this study utilized agent-based simulation to explore the non-linear dynamic mechanism underlying how teacher-student proximity, teacher feedback, and near-seated peer groups affect classroom engagement, thereby shedding light on the evolutionary features of classroom engagement. According to the results, the teacher's positive feedback promoted an S-shaped increase in classroom engagement, and the closer a student sat to the teacher, the greater the increase was. The level and homogeneity of near-seated peer group engagement were predictors of changes in classroom engagement. Moreover, the proximity of students to the teacher, teacher feedback, and near-seated peer groups had a joint effect on student engagement. The compensation effect of the teacher's positive feedback on the impact of low-engagement, near-seated peer groups was weaker than that of highly engaged, near-seated peer groups on the effects of the teacher's negative feedback. This suggests that the model of teacher-student proximity and teacher feedback effects differed from that of near-seated peer group influence, and the two interacted and showed asymmetry.